Sustainability Implication of the Lestari Tea Certification Program Implementation on the Tea Small Holder at Campaka Subdistrict Cianjur - Hutagalung, Tulus Bangun (Jurnal Penelitian Teh dan Kina, 2016)
In order to increase the income of tea smallholder and maintain the sustainability of tea, Dewan Teh Indonesia collaborated with Business Watch Indonesia in establishing a local certification scheme that is called as Lestari Tea Certification Program. This certification program has been conducted at some areas since 2011 until 2013 and one of the areas was Campaka sub-district, Cianjur. This research aimed at analysing the susÂtainability impact of the certification program by questionnaire and interview data collection. Analysing sustainability is conducted by using Mann-Whitney test by comparing the perÂception of the tea farmers who participated and those who didnât participate on the certification program. Independent sample t test is also used to test the differentiation of the mean the income and transportation vehicle and comÂmunication asset between member of Tea Lestari Certification Program and those who are not. Moreover, logistic regression is used to know which variable more influence the probability for the tea farmers to join the certification program. The output of Mann-Whitney test shows that there is significant difference on the aspect of environment, economy, and social between tea farmers that participated and those who didnât participate on the certification program. Logistic regÂression output shows that education level, size of plantation land, and location of village influence the probability of the tea farmers whether to join or not join the Lestari Tea Cerfication Program.